Perbandingan Fungsi Media Komunikasi Elektronik Dalam Menyampaikan Informasi Kepada Khalayak: Televisi, Radio, Internet - Gita Faradilla Rizky Nurjannah; Dr. Umi Halwati; Dr. Sulchan Chakim (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2023)
Electronic media are media that use electronics or electromechanical energy for end users to access their content. This term is in contrast to static media (especially print media), which, although often generated electronically, do not require electronics to be accessed by end users. There are several kinds of electronic media: television, radio, and the internet. News information today is very different from time to time. People want news that has educational elements as a means of learning, as well as accurate and fast current news information. The main purpose of using electronic media to get good news is to provide good information and make it easier for people to be more efficient and get more news from around the world.